2017
DOI: 10.4253/wjge.v9.i4.183
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic balloon catheter dilatation via retrograde or static technique is safe and effective for cricopharyngeal dysfunction

Abstract: AIMTo evaluate the safety and efficacy of upper esophageal sphincter (UES) dilatation for cricopharyngeal (CP) dysfunction. To determine if: (1) indication for dilatation; or (2) technique of dilatation correlated with symptom improvement.METHODSAll balloon dilatations performed at our institution from over a 3-year period were retrospectively analyzed for demographics, indication and dilatation site. All dilatations involving the UES underwent further review to determine efficacy, complications, and factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…[ 29 , 30 ] Recently, it was reported that EBD using the retrograde method was also safe and effective for CPD, compared with the classic static technique. [ 31 ] However, dilatation using 1 balloon or bougie would not be effective in patients with UES relaxation dysfunction because the UES is not round. [ 32 ] Pilot data suggest that EBD using 2 simultaneous controlled radial expansion balloon dilators is feasible, safe, and effective.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 , 30 ] Recently, it was reported that EBD using the retrograde method was also safe and effective for CPD, compared with the classic static technique. [ 31 ] However, dilatation using 1 balloon or bougie would not be effective in patients with UES relaxation dysfunction because the UES is not round. [ 32 ] Pilot data suggest that EBD using 2 simultaneous controlled radial expansion balloon dilators is feasible, safe, and effective.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Such a dilatation procedure exerts radial and axial (sheering) forces to the UES with the distended balloon and a pull-up maneuver, similar to the endoscopic balloon catheter dilatation introduced in previous reports. [10]…”
Section: Discussionmentioning
confidence: 99%
“…CPD may have led to severe dysphagia and aspiration [16]. Symptoms of CPD can range from a globus sensation to oropharyngeal dysphagia manifested by regurgitation, coughing choking and recurrent aspiration [17]. The sensory stimuli that trigger and modulate swallowing include tactile stimuli (light and heavy pressure, air puffs, different bolus volumes and viscosities), chemical stimuli (water, other solutions, cations and anions), thermal stimuli and combined stimulus modalities [1821].…”
Section: Discussionmentioning
confidence: 99%